PLURALITY AND DIVERSITY AS UNITY IN THE NEW TESTAMENT: ECCLESIOLOGICAL AND ECUMENICAL IMPLICATIONS FOR ANGLICAN–ROMAN CATHOLIC RELATIONS - Obu, Samuel (Asian Horizons, 2019)
Christianity started as a radical movement in Judaism, later spread among non-Jewish communities, and became a ‘universal’ phenomenon. As it encountered different cultures at different times, the pluralistic nature of Christianity broadened. The singular event that threw wide open the floodgates of pluralism was the Reformation. Influenced by political, doctrinal, cultural, intellectual and economic factors, many Christian denominations were founded. Unfortunately, these Christian confessions were at times antagonistic towards each other, condemned and persecuted each other and even waged wars against each other. This dark history of Christianity is against the prayer of Jesus to the Father for his followers: “that they may all be one” (Jn 17:21) One of the means of handling the crisis of disunity of Christians is an attention to the developmental manner of being church, rooted in the person of Jesus Christ and guided by the gospel. With particular attention to the Anglican-Roman Catholic relations, this article presents a theological dogmatic approach that sees the unity of the ecclesial community as genuine plurality and legitimate diversity.